Sophocles: Oedipus the King - Film for the Humanities (Firm). (Princeton, N.J. Films for Humanities, 1975)
A play that examnines classical Greek theater in general and Sophocles work in particular.
Performed in the 5th century B.C. Theatre at Amphiaraton of the Athena Classical Theatre Company
VHS
Translation of Oedipus the King by Stephen and Michael Mantell; Edited by Carlo.
The voices, Anthony Quayle as Dionysus and the narrator; James Mason as Oedipus; Claire Bloom as Jocasia.
Keywords: Mantell, Harold; Oedipus (Greek mythology) in literature; Greek drama (Tragedy) -- Translation into English; Sophocles -- Oedipus Tyrannus